PENGARUH KOMITE AUDIT, UKURAN PERUSAHAAN DAN FEE AUDIT TERHADAP KUALITAS AUDIT PADA PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2017-2022 - indriyani, jihan Putri; Hasanah, Neneng (Jurnal Nusa Akuntansi, 2024)
This research aims to find out and provide empirical evidence regarding the influence of the audit committee, company size and audit fees on audit quality. The population in this research is manufacturing companies operating in the Food and Beverage Sub Sector Companies Listed on the Indonesian Stock Exchange 2017-2022. the influence is partial or simultaneous. This research uses a quantitative approach and uses associative methods. The samples used were 10 samples of companies which used secondary data obtained from the Company's Financial Reports. The method used is statistical testing which includes logistic regression testing, hypothesis testing and coefficient of determination. The research results show that the audit committee partially has no effect on audit quality using the eviews version 9 and Microsoft Excel applications. The research results show that partially the audit committee has no effect on audit quality, partially company size has no effect on audit quality, partially audit fees have an effect on audit quality, simultaneously, audit committee, company size and audit fees have an effect on audit quality